LAW AND MORALITY: THE LESSONS OF PLATO AND ARISTOTLE - L. Fastiggi, Robert (Journal of Dharma, 1979)
The question of the relationship between law and morality has become a very important issue in contemporary philosophy. The task of exploring and defining this relationship is crucial in a world in which laws have become so numerous and complex and morality has become so relative and confused. Indeed, the very magnitude of laws and the intricacies of legal terminology have created a tremendous cloud of obscurity over the interdependence of legislation, justice and moral virtue. The practice and study of law have become so specialized that it is uncertain whether people even recognize a relationship between law and morality.